Atypical Lipomatous Tumors: Does Our Inconsistent Terminology Have Patient Repercussions? Results of a Meta-Analysis. (May 2019) - Fourman, Mitchell S.; van Eck, Carola F.; Weiss, Kurt R.; Goodman, Mark A.; McGough, Richard L.
Abstract : Objectives: Misnaming low-grade lipomatous tumors poses a clinical and medicolegal challenge, potentially subjecting patients to expensive and unnecessary surgeries. The terms atypical lipomatous tumor (ALT) and "well-differentiated" liposarcoma (WDL) have been used interchangeably in pathology reports, scholarly works and consensus recommendations, creating vagaries between low-virulence extremity tumors and retroperitoneal disease with metastatic potential. Methods: A systematic review was performed on all studies that reported on the local recurrence rate and metastasis of ALTs and WDLs in living human subjects. Local recurrence and metastases were compared using Fisher's Exact Test. Results: In total, 20 studies evaluated ALTs (n=936), whereas 13 studied WDLs (n=626). Mean follow-up was 6.6±2.0 years (median, 7.0 y). No metastatic disease was observed among ALTs, whereas 15 patients with WDLs (2.7%, P <0.0001) had metastases. The local recurrence rate of ALTs was significantly lower than WDLs after both marginal (15.1%, 141/936 vs. 46.0%, 288/626, P <0.0001) and wide excisions (3.3%, 2/59 in ALT vs. 17.4%, 19/109, P =0.007). Conclusions: ALT should be reserved for extremity lesions meeting appropriate histopathologic criteria that represent nonmetastatic disease, reducing over-diagnosis, over-treatment, and patient risk.